Newly Synthesized Pyridinium Salt Based Tricationic Surfactants as Corrosion Inhibitor for Carbon Steel in 1.0 M HCl Medium - Ozturk, Serkan; Gece, Gokhan; Yildirim, Ayhan; Gerengi, Husnu (Pleiades Publishing Ltd, 2023)
Two pyridinium salt based tricationic surfactants were synthesized using quarternization reaction. The characterization of the surfactants were done by spectroscopic methods (FT-IR and NMR). Some pysicochemical properties like critical micelle concentration, surface tension at critical micelle concentration, Gibbs free energy of micelization, foam height, foam stability and emulsion stability were measured. The anticorrosion properties of the synthesized compounds were investigated by gravimetric measurements. In corrosion tests, where both compounds showed inhibitory activity against the corrosion of carbon steel in 1.0 M HCl environment, while the inhibition efficiency of the compound containing 6 carbon atoms in the long chain was determined in the range of 62-76%, those of the compound containing 8 carbon atoms in the long chain was found in the range of 85-93%. On the other hand, density functional theory (DFT) calculations were applied to arrive at basic molecular/electronic level scale details about the synthesized compounds, in addition to the surface images of the metal obtained by scanning electron microscopy to support the corrosion prevention results.
Keywords: synthesis; pyridinium; tricationic corrosion inhibitor; DFT; HCl medium